Leishmaniasis in Eurasia and Africa: geographical distribution of vector species and pathogens. Issue 5 (22nd May 2019) - Cunze, Sarah; Kochmann, Judith; Koch, Lisa K.; Hasselmann, Korbinian J. Q.; Klimpel, Sven
Abstract : Leishmaniasis is a vector-borne disease with a broad global occurrence and an increasing number of recorded cases; however, it is still one of the world's most neglected diseases. We here provide climatic suitability maps generated by means of an ecological niche modelling approach for 32 Phlebotomus vector species with proven or suspected vector competence for five Leishmania pathogens occurring in Eurasia and Africa. A GIS-based spatial overlay analysis was then used to compare the distributional patterns of vectors and pathogens to help evaluate the vector species–pathogen relationship currently found in the literature. Based on this single factor of vector incrimination, that is, co-occurrence of both vector and pathogen, most of the pathogens occurred with at least one of the associated vector species. In the case of L. donovani, only a not yet confirmed vector species, P. rodhaini, could explain the occurrence of the pathogen in regions of Africa. Phlebotomus alexandri and P. longiductus on the other hand, proven vector species of L. donovani, do not seem to qualify as vectors for the pathogen. Their distribution is restricted to northern latitudes and does not match the pathogen's distribution, which lies in southern latitudes. Other more locally confined mismatches were discussed for each pathogen species. The comparative geographical GIS-overlay of vector species and pathogens functions as a first indication that testing and re-evaluation of some pathogen–vector relationships might be worthwhile to improve risk assessments of leishmaniasis.